Penggunaan Aplikasi Musescore 3 Dalam Kegiatan Ekstrakurikuler Biola di Jurusan Musik Gereja STAKPN Sentani - Magdalena Susana Marlissa (Program Studi Pendidikan Musik FBS UNP, 2024)
Purpose: MuseScore 3 is a very useful tool for students who are learning the violin. The purpose of this study is to find out how the MuseScore 3 application can facilitate learning and practice playing the violinamong students, and to find out the extent to which MuseScore 3 can improve their violin playing ability. Through this research, the presence of MuseScore 3 in violin learning at the STAKPN Sentani Church Music Department can be comprehensively studied. Method: The research method used is qualitative, going through the stages of data reduction, data presentation, and verification. Results and Discussion: Basically, students have difficulty playing the violin using sheet music alone, but when using MuseScore 3, they are greatly assisted in the process of learning to play the violin. Conclusion: What students feel when using this application is that all the worries and difficulties experienced when playing the violin are significantly alleviated, and they can recognize notation easily.